Assessment of the Relationship between Oral Health Behavior, Oral Hygiene, and Gingival Status of Adolescent Tobacco Consumers in Ranchi, Jharkhand: A Comparative Study. (10th September 2021) - Kumar, Sandeep; Kumar, Arunoday; Gupta, Anjali; Singh, Siddharth Kumar; Gupta, Abhishek; Mehta, Palkin
Abstract : Background . Tobacco consumption is very prevalent in India and associated with a number of oral health problems. Good oral health behavior plays a significant role in improving oral hygiene status. Objectives . To assess the relationship between the oral health behavior, oral hygiene, and gingival status of adolescent tobacco consumers (smoke/smokeless form) and to compare it with that of the nonconsumers of tobacco in the same age group, who were selected from the OPD of Dental Institute, RIMS. Methods . This was a cross-sectional study carried out in Ranchi. The study included a total of 400 adolescents who were reported to be consumers of tobacco and 400 adolescents who were nonconsumers of tobacco. The oral health behavior was assessed using HU-DBI. The plaque and gingival scores were assessed using standardized indices. Data were analyzed using the Chi-square test, independent sample t -test, and Pearson's correlation. The significance level was set at p ≤ 0.05 . Results . The majority of tobacco consumers were found to have poor plaque scores as assessed using the plaque index. As assessed by the gingival index, the majority of the tobacco consumers were found to have a severe form of gingivitis. The mean plaque score (2.38 ± 0.51, p value <0.001) and the mean gingival score (2.6 ± 0.63, p value <0.001) were significantly higher in tobacco consumers. The mean HU-DBI score was significantly higher in non-tobacco consumers (8.3 ± 1.60, p value <0.001). It was observed that the gingival and plaque scores have a significant negative correlation with the HU-DBI score. The majority of tobacco consumers were worried about the staining of teeth and bleeding from gums. A dental visit for a routine preventive check-up was reported to be rare in both groups. Conclusion . The oral hygiene and gingival status were significantly poor in tobacco consumers compared to non-tobacco consumers. As the oral health behavior of the participants improved, the plaque and gingival scores reduced significantly.